Peningkatan Kualitas Pengelola dalam Menyusun Laporan Keuangan pada BUMDes Ngudi Makmur Desa Sundoluhur Kecamatan Kayen Kabupaten Pati - Solihin, Khabib; Ami'in, Siti Nur; Jumadi, Jumadi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
As a business entity managed by the community and village government, BUMDes must make financial reports of all business units as a form of accountability for managing funds provided by the village government to BUMDes. In general, BUMDes bookkeeping principles are not much different from bookkeeping financial statements at other institutions in general, BUMDes must record all financial transactions systematically according to the accounting system. Based on the results of observations and interviews, the problem faced by BUMDes in Sundoluhur village, Kayen sub-district, Pati district is the lack of knowledge and ability of BUMDes managers in compiling BUMDes financial reports correctly according to accounting standards. Based on the results of these observations, this service is carried out to increase knowledge and ability for BUMDes managers in preparing BUMDes financial reports properly and correctly in accordance with Financial Accounting Standards - Entities Without Accountability (SAK ETAP). This activity is carried out through several stages including planning, training, and assistance in preparing BUMDes financial reports. The result of this activity is that the BUMDes management is able to prepare financial reports properly and correctly in accordance with accounting standards by using the financial applications provided.